The Effectiveness of Microsoft Teams, Zoom and Canvas for Students. Case Study: three High Schools in Ho Chi Minh City - Anh, Pham Quynh; Uyen, Nguyen Tam; Dung, Mai Thi Thuy (VNU Journal of Science: Education Research; Vol 39 No 1DO - 10.25073/2588-1159/vnuer.4694, 2023)
Vietnamese education has been significantly affected by the Covid-19 pandemic, especially in the 2021-2022 academic year, as seen by the widespread use of online learning from primary through graduate levels across a variety of learning platforms. However, each platform has its own strengths and also exposes certain limitations. This article examines the effectiveness of three platforms used in e-learning for general education: Zoom, Microsoft Teams, and Canvas through the lens of 240 students from one public high school and two private high schools in Ho Chi Minh City. The study employs a mixed approach, mainly qualitative. Research results have reflected the advantages, disadvantages, and solutions to improve each software and synthesize the elements that an online learning application needs.